Effect of Fiber, Cement, and Aggregate Type on Mechanical Properties of UHPC - Shahrokhinasab, Esmail; Looney, Trevor; Floyd, Royce; Garber, David (Civil Engineering Journal, 2021)
Ultra-High Performance Concrete (UHPC) is a new class of concrete that differentiates itself from other concrete materials due to its exceptional mechanical properties and durability. It has been used in structural rehabilitation and accelerated bridge construction, structural precast applications, and several other applications in the past decades. The mechanical properties of UHPC include compressive strength greater than 124 MPa (18 ksi) and sustained post cracking tensile strength greater than 5 MPa (0.72 ksi) when combined with steel, synthetic or organic fibers. Proprietary, pre-bagged mixtures are currently available in the market, but can cost about 20 times more than traditional concrete. This high price and the unique mixing procedure required for UHPC has limited its widespread use in the US and has motivated many researchers to develop more economical versions using locally available materials. The objective of this study was to investigate the effect of different proportions of typical UHPC mixture components on the mechanical properties of the mixtures. Particle packing theory was used to determine a few optimal mixture proportions and then modifications were made to investigate the effect. A compressive strength of around 124 MPa (18 ksi) was achieved without using any quartz particles in the mixture design.Â Doi: 10.28991/cej-2021-03091726 Full Text: PDF